A Study of the production system of Burlington Industries Philippines,Inc. - Claridad, Ma. Lourdes Bernadette V. (College of Engineering, 2002)
Burlington Industries Philippines, Inc. is the leadingmanufacturer of a full range of socks in the country. It believes in providing total customer satisfaction through product availability, on-time delivery and consistent quality of services. Although it is the leader in the industry, the company feels there is still room for improvement in their existing system. The study aims to document the company's present system , identify problem areas, and recommend alternatives. Burlington produces a wide variety of socks which can be classified according to length, texture, and design. Aside from the Burlington brand, it also carries the Puma and Bally Brands. The company also manufactures socks exclusiveley for companies, such as Guess? and Bench. THe company's production department is divided into 5 sections according to the type of socks they produce. The layout was evaluated from a technical/engineering perspective. The production of socks involves three main processes; namely, knitting, looping/linking/seaming, boarding, and finishing. Some socks undergo dyeing and embroidery depending on the design. Input measures were used to evaluate the plant's capacity. It was determined that the actual number of machines is more that sufficient to handle the company's production requirements. Forecasting is done by the promo coordinators from concessionaires. The 10-fast moving designs per category is identified and the forecast for the following month is taken to be approximately equal to the preceding month. The company also uses naive forecasting o determine production levels for products with seasonal demand. Raw materials are ordered from 12different suppliers, 3 of which are based abroad. Ordering of yarns is done every month. However, due to space constraints, arrival of order is staggered. The company employs over 200 workers. Contractual workers are hired and overtime is done during periods of high production levels. Each worker works for 1 shift per day (there are 2 8-hour shifts per day). Retiring employees are given benefits corresponding to the number of years in service to the company. A series of plant visits and interviews were done to evaluate the situation of the plant and identify its major concerns. The major problems were identified to be: high cost of labor, high finished goods inventory, and delays in production. The root causes of the problems were identified: ineffective ordering policy, absence of aggregate planning techniques, and ineffective forecasting techniques. Alternatives were generated and evaluated. The optional replacement policy with a fixed period of 1 week was recommended for the company's raw materials inventory system. The inventory position is reviews at one week intervals. A new order must be done to bring the inventory position to the target level. The exponential smoothing method was recommended as the appropriate forecasting technique for the company. Using the measures of forecast errors, this method yielded lower values than the multiplicative seasonal index method. The Chase Strategy with Overtime was recommended as this resulted in the least labor cost compared to the Chase Strategy without overtime and the Level Strategy.